The long terminal crisis of the Venezuelan oil rentier model and the deep crisis currently facing that country - Lander, Edgardo (2018)
This essay seeks to present and explain the most serious economic and political crisis that Venezuela has experienced since civil wars of 19th century. Also, it explores the political, economic and social crisis in a exhaustion cycle of a rentier model with a chaotic management of public administration, at a time when popular sectors are organizationally weakened and political opposition tries violent ways to worsen civil confrontations in this second decade of the 21st century. Finally, it elaborates several explanatory postulates about the situation of the movements and popular organizations which are facing the crisis.